2007
DOI: 10.1111/j.1360-0443.2007.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

The transition from injection to non‐injection drug use: long‐term outcomes among heroin and cocaine users in New York City

Abstract: The transition from injection to non-injection use appears to be relatively stable behavior change for many former injectors, who report a decade or more without injecting. Developing a greater understanding of the transition from injection to stable non-injection drug use may provide insights into the natural histories of drug use and addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 31 publications
6
57
0
2
Order By: Relevance
“…However, in another prospective study conducted in Iran, the switching from IDU to NIDU was reported to be more prevalent than the other way around (31). At least three studies from United States (New York), the Netherlands (Amsterdam), and India (Chennai) have corroborated the possibility of reverse transition, as well (13,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, in another prospective study conducted in Iran, the switching from IDU to NIDU was reported to be more prevalent than the other way around (31). At least three studies from United States (New York), the Netherlands (Amsterdam), and India (Chennai) have corroborated the possibility of reverse transition, as well (13,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the window of opportunity to intervene after someone starts injecting drugs is short (12). Preventing initiation of injection and promoting the transition from injecting to non-injecting drug use can therefore be considered primary methods for preventing multiple infectious diseases and other health problems (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…31 Research indicates that sexual transmission is surpassing injection transmission as the means of transmission among NYC IDUs; a 2009 study by Des Jarlais et al found that female, black, and younger ( < 40 years of age) IDUs were disproportionately infected with herpes simplex type 2. 32 A study of drug use in NYC, found that for those who had transitioned from injection to non-injection drug use, the duration of abstinence from injection was approximately 10 years; 33 likewise, the time since last injection for all those who reported ever injecting drugs in the current study was a median of 12 years (IQR: 3, 23), indicating a greater potential for heterosexual transmission. Moreover, former injection drug users may be less likely than their current injector counterparts to be targeted by public health programs, which encourage regular testing for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In Vancouver, willingness to use an inhalation room was associated independently with working in the sex trade, sharing crack pipes, having crack pipes confiscated by police, smoking crack in public places and having burns from hurried drug consumption [9]. As many cities are witnessing decreasing numbers of drug injectors but increasing numbers of people who smoke/snort drugs [18], SIRs warrant a close second look.A powerful case can be made in support of SIRs based upon the personal experience of one of the authors of this commentary (J.R.N. ), who helped to coordinate a drug consumption facility in the city of Bilbao, in Spain's Basque region.…”
mentioning
confidence: 99%
“…In Vancouver, willingness to use an inhalation room was associated independently with working in the sex trade, sharing crack pipes, having crack pipes confiscated by police, smoking crack in public places and having burns from hurried drug consumption [9]. As many cities are witnessing decreasing numbers of drug injectors but increasing numbers of people who smoke/snort drugs [18], SIRs warrant a close second look.…”
mentioning
confidence: 99%